The Characterization of the Main Protagonist in the Movie “Ready or Not” - Ni Kadek Nefiari; I Made Perdana Skolastika (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study analyzes the characterization of Grace, the main protagonist in ” Ready or Not” (2019), a movie about Grace, a newlywed who must survive from deadly game of hide-and-seek on her wedding night. This study used a qualitative descriptive method to identify and understand Grace’s character and used the observation method for the data collection. The data was collected from the movie, and accessed through the “Loklok” platform. The characterization of Grace was analyzed from three dimensions: psychological, sociological, and physiological, based on the theory of Wellek and Warren (1962). The study found the characterization of Grace Le Domas's transformation from naive to survival. Physiologically, Grace’s appearance shifts dramatically from a pristine wedding dress to a tattered, bloodied garment, symbolizing her transition through the trauma of her ordeal. Psychologically, her transformation from innocence to a determined survivor emphasizes the movie's exploration of the psychological effects of extreme tension and survival instincts. Sociologically, Grace’s lower socio-economic status compared to the wealthy Le Domas family emphasizes her struggle and effect on her decisions, highlighting the movie's critique of class disparity. Her transformation from innocence to survival, and eventually to violence, illustrates the transformative potential of horror narratives to explore the darker sides of human nature. Grace's characterization is important, it reflects the movie's larger themes, which include the corruption of wealth, the breaching of moral and social norms, and survival. This study contributes to the field of literary analysis by enriching the understanding of character development, especially in horror narratives.